Visualizing the urethra by magnetic resonance imaging without usage of a catheter for radiotherapy of prostate cancer. (April 2021) - Yoshimura, Takaaki; Nishioka, Kentaro; Hashimoto, Takayuki; Fujiwara, Taro; Ishizaka, Kinya; Sugimori, Hiroyuki; Kogame, Shoki; Seki, Kazuya; Tamura, Hiroshi; Tanaka, Sodai; Matsuo, Yuto; Dekura, Yasuhiro; et al.
Highlights: Post urination MRI is useful for urethra-sparing radiotherapy treatment planning. This prospective clinical trial included 11 prostate cancer patients. Post urination MRI is the identification method of prostatic urinary tract in non-invasive manner. Abstract: The urethra position may shift due to the presence/absence of the catheter. Our proposed post-urination-magnetic resonance imaging (PU-MRI) technique is possible to identify the urethra without catheter. We aimed to verify the inter-operator difference in contouring the urethra by PU-MRI. The mean values of the evaluation indices of dice similarity coefficient, mean slice-wise Hausdorff distance, and center coordinates were 0.93, 0.17 mm, and 0.36 mm for computed tomography, and 0.75, 0.44 mm, and 1.00 mm for PU-MRI. Therefore, PU-MRI might be useful for identifying the prostatic urinary tract without using a urethral catheter. Clinical trial registration: Hokkaido University Hospital for Clinical Research (018-0221).